Combinatorial Design Of Virtual Sialic Acid Analogues Against Influenza A Hemagglutinin Using Structure And Fragment Based Approaches - Al-Qattan, Mohammed Noor Al-Deen (2009)
In this study molecular modeling techniques were used to design databases of virtual SA analogues by a single substitution at either of C2, C5 or C6 positions of SA scaffold. Dalam kajian ini, kaedah pemodelan molekul telah digunakan untuk mereka bentuk pangkalan data analog maya SA dengan penggantian tunggal sama ada pada kedudukan C2, C5 atau C6 rangka SA.